Emerging role of transient receptor potential (TRP) ion channels in cardiac fibroblast pathophysiology - Gwanyanya, Asfree; Mubagwa, Kanigula (Frontiers in Physiology, 2022)
Cardiac fibroblasts make up a major proportion of non-excitable cells in the heart and contribute to the cardiac structural integrity and maintenance of the extracellular matrix. During myocardial injury, fibroblasts can be activated to trans-differentiate into myofibroblasts, which secrete extracellular matrix components as part of healing, but may also induce cardiac fibrosis and pathological cardiac structural and electrical remodeling. The mechanisms regulating such cellular processes still require clarification, but the identification of transient receptor potential (TRP) channels in cardiac fibroblasts could provide further insights into the fibroblast-related pathophysiology. TRP proteins belong to a diverse superfamily, with subgroups such as the canonical (TRPC), vanilloid (TRPV), melastatin (TRPM), ankyrin (TRPA), polycystin (TRPP), and mucolipin (TRPML). Several TRP proteins form non-selective channels that are permeable to cations like Na+ and Ca2+ and are activated by various chemical and physical stimuli. This review highlights the role of TRP channels in cardiac fibroblasts and the possible underlying signaling mechanisms. Changes in the expression or activity of TRPs such as TRPCs, TRPVs, TRPMs, and TRPA channels modulate cardiac fibroblasts and myofibroblasts, especially under pathological conditions. Such TRPs contribute to cardiac fibroblast proliferation and differentiation as well as to disease conditions such as cardiac fibrosis, atrial fibrillation, and fibroblast metal toxicity. Thus, TRP channels in fibroblasts represent potential drug targets in cardiac disease.